Planeamento da carreira, comportamento e rendimento académico no ensino básico - Taveira, Maria do Céu (2017)
Career planning stimulates personal competence and coping with career and future. We analyse the simultaneous relationship between career planning and academic behaviour and performance. Participants were 446 students from the 5th year (231, 52.2% boys), aged nine to 13 years old (M = 10.23, SD = 0.49). A demographic questionnaire and the planning subscale of the Childhood Career Development Scale were used. Results evidenced two different career profiles: the constructive, with higher planning and positive outcomes in academic behaviour and performance; the vulnerable, with lower planning, behavioural problems, more learning difficulties, and school retention. Keywords: career development, childhood, career planning, academic performance.O planeamento de carreira estimula sentimentos de competência pessoal que habilitam a lidar com a carreira e o futuro. Analisa-se a relação simultânea entre planeamento da carreira e comportamento e desempenho académico. Participaram 442 alunos do 5º ano (231, 52.2% rapazes), com idades entre nove e 13 anos (M = 10.23, DP = 0.49). Utilizou-se um questionário de identificação e a subescala planeamento da Childhood Career Development Scale. Os resultados evidenciam dois perfis de carreira: o construtivo, com mais planeamento, comportamento e resultados académicos positivos; o vulnerável, com o planeamento mais baixo, problemas comportamentais, mais dificuldades na aprendizagem e retenções. Palabras chave: desenvolvimento de carreira, infância, planeamento da carreira, desempenho académico.